Pengembangan E-Modul Interaktif untuk Discovery Learning pada Pembelajaran Mekanika Teknik dan Elemen Mesin - Marko Ayaki Lumbantobing; Sudji Munadi; Bernardus Sentot Wijanarka (Department of Mechanical Engineering Education, 2019)
The purpose of this research is to find out the feasibility of e-module for discovery learning users' responses to the use of the e-module. This development research follows the development stages of the ADDIE model. Likert scale with four variations of answers was used. Research data were analyzed using a quantitative-descriptive analysis. The result shows that the use of an e-module for discovery learning has met the criteria of feasibility within the